A numerical study on wave overwash on viscoelastic floating covers using smoothed particle hydrodynamics - Liu, Xiaodong (2024)
Large floating covers on the water surface, such as very large floating platforms or ice covers in the marginal ice zone, can exhibit viscoelastic response during their interactions with progressive gravity waves. When the wave magnitude is exceedingly large, overtopping can also occur with wave overwash appearing on top of the cover. In the present study, we investigate the numerical simulations of the transient wave overwash on the viscoelastic floating cover using the smoothed particle hydrodynamics (SPH) approach. In particular, a new numerical scheme is derived whereby the floating cover is represented through discretization into elementary rigid sections interconnected via rotational hinges with damping, with the hinge characteristics matching the viscoelastic properties of the cover. Both laminar viscosity and sub-particle-scale turbulence model for the water motion are considered in the SPH simulation. For validation, experiments of wave interaction with a viscoelastic floating cover with and without wave overtopping were also performed in the present study. The results show that SPH can predict well the wave reflection and transmission by the floating cover with transient overwash on top, as well as the threshold of incident wave steepness that initiates the wave overtopping. Overall, the current study demonstrates for the first time that SPH approach can be an effective tool to solve hydro-viscoelasticity problems by simulating the highly complex wave interactions with viscoelastic floating covers including overtopping.